Facilitating Patient Recruitment Process for Research - Li, Bing; Manns, Braden; Raso, Jim; Saunders, Terry; Bakal, Jeff (International Journal of Population Data Science, 2018)
Introduction The Assessing outcomes of enhanced Chronic disease Care through patient Education and a value-based formulary Study (ACCESS) conducted from the University of Calgary trial is seeking 4700 low-income Albertans over the age of 65 years at high risk for cardiovascular morbidity and mortality. Recruitment efforts using advertising, conventional methods including posters and brochures in pharmacies have been challenging. The use of admail was attempted but fewer than 260 people (out of nearly 122,000 letters mailed) were enrolled. Objectives and Approach The objective was to determine if linking data collected by Alberta Health Service (AHS) could identify eligible patients and facilitate recruitment for the study. We extracted cohorts of data based ICD codes. These patient’s data were linked with Admission, Discharge and Transfer (ADT) and Master Patient Index (MPI) data to pull patient’s names, addresses and postal codes. Deceased and previously contacted patients were eliminated. The final patient name-list from the Analytics team was merged with a notification letter from Research Administration and sent by the data communication team to candidate patients. Interested patients contacted the researchers. Once informed consent was obtained, the data communication team sent the study questionnaire to the patients directly. Results 30,343 eligible patients were identified in Calgary and 23,305 in Edmonton. Out of 13825 people contacted, 304 people were enrolled into the study – a significantly higher rate than using other mail-based methods. Conclusion/Implications By linking various health administrative data, we assisted researchers to identify potential participants who would otherwise be inaccessible and geographically dispersed across Alberta. This effectively facilitated the recruitment process and enabled patients from across the province to participate with minimal investments.